Design and analysis of controllers for high voltage gain DC-DC converter for PV panel - S. Nagaraj; R. Ranihemamalini; L. Rajaji (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Bidirectional high gain DC-DC buck boost converter is a virtual interface among PV source and inverter fed motor drive. In this article, a PV panel integrating a non-isolated bidirectional DC/DC converter that has high voltage gain voltage and a 3 phase three level DC/AC inverter is projected. It highlights the comparison between proportional integral controller (PIC), fractional order proportional integral derivative Controller (FOPIDC) and fuzzy logic controller (FLC) based Bidirectional DC/DC Power Converter System (BDDPCS). The design, model and simulation using SIMULINK of open loop BDDPCS and closed loop PIC, FOPIDC and FLC based BDDPCS are done and the results are discussed. The findings indicate higher performance for FLC based control of BDDPCS. The proposed BDDPCS has merits such as bidirectional power transferability, lesser hardware count with enhanced dynamic response. The hardware of BDDPCS is tested and the experiment result is compared in association with simulation results.